PERBANDINGAN PEMBIAYAAN USAHA MIKRO KECIL DAN MENENGAH (UMKM) BANK SYARIAH DAN BANK KONVENSIONAL (STUDI KASUS PADA BANK SYARIAH MANDIRI DAN BANK MANDIRI) - Esti Damayanti, SE., M.Si. (Jurnal Akuntansi dan Bisnis Krisnadwipayana, 2016)
The purpose of this research is to give an idea how the financing or credit on SME segment by Islamic banks and conventional banks in order to note also the differences and similarities between the two. The objects used in this study is the Islamic Bank of Syariah Mandiri and Bank Mandiri on the grounds both banks are commercial banks with the largest asset category for Islamic banks and conventional banks. Basically, the Indonesian economy can not be separated from SMEs considering this type of effort to master the many business sectors in Indonesia with a total of over 90%. In addition, SMES have an important role in economic development because the absorption rate is relatively high labor and capital needs of small invesment, SMEs can adapt and arespond flexibly to changing market conditions. This makes the SMEs are not vulnerable to external changes. This in one reason why the banks started to direct the disbursement of funds to the SMES segment as the business sector, SMEs are considered as the most resistant to the crisis and has been proven at the time of crisis in 1997. At that SMEs who are considered as a crutch and economic savior. This condition is very different from the past era that focuses on corporate disbursements to be quicker and greater the benefit. Therefore, learning from past experience of the crisis that has so many banks in Indonesia began to glance at the micro, small and medium enterprise in distributing the funds considering this kind of loan is more secure. This research describes the financing or loans made by banks on financing products, processes and analyzes the the distribution of financing, development financing portfolio of SMEs and obstacles in delivering finance companies. The time period used was from 2007 until 2009. The results of this research show that in channeling finance/ SME loans by the Bank Syariah Mandiri and Bank Mandiri there is a difference in terms of product and criteria for financing, development financing portfolio of each bank is note the same. While the various obstacles faced by both banks can be said is quite similar although there are slight differences, so is the process of distribution and financing analysis.